Promoting higher-valent pediatric combination vaccines in China: challenges and recommendations for action - Jiuling Li; Shu Chen; Edwin Asturias; Shenglan Tang; Fuqiang Cui (BMC, 2024)
Abstract Many countries have adopted higher-valent pediatric combination vaccines to simplify vaccination schedules and minimize health expenditures and social costs. However, China is conservative in the use of pediatric combination vaccines. By reviewing and synthesizing quantitative and qualitative data, in this commentary we identify gaps and challenges to combination vaccine use and make recommendations for promoting use of higher-valent pediatric combination vaccines in China. Challenges are in four dimensions: (1) legislation and regulation, (2) immunization schedule design, (3) vaccine awareness and price, and (4) research and development capacity. To optimize the use of combination vaccines to reduce vaccine-preventable disease burden, we make recommendations that address key challenges: (1) develop policies and regulations to strengthen enforcement of the Vaccine Administration Law and remove regulatory hurdles that hinder combination vaccine research and development, (2) establish an evidence-informed policy-making mechanism for combination vaccines, (3) resolve immunization schedule conflicts between monovalent and combination vaccines, and (4) implement effective interventions to increase vaccine awareness and reduce price. Graphical Abstract